Manejo agroecológico do capim-elefante sob pastejo, consorciado com culturas de ciclo estival e hibernal - Sobczak, Marinês Fátima (2004)
The work was conducted in Santa Maria, RS, Brazil, with the objective of to evaluate an elephantgrass pasture (Pennisetum purpureum Schum.) var. Merckeron Pinda, under rotational grazing, during the agricultural year of 2002. The elephantgrass was established in lines separated by three meters, at October of 2001 on a 0,33 ha area. Organic fertilization was used in form of swine (70 kg/ha of N) and bovine (30kg/ha of N) manure applied at October of 2001 and January of 2002, respectively. During the agricultural year two experimentations were performed, one at summer period (January 16th until April 17th of 2002) and another in winter period (June 12th until October 14th of 2002). The area was divided in two paddocks. In summer period the pasture was constituted by elephantgrass (at lines) and spontaneous growing species (in the space between lines). The utilization period of pasture was from 01/16 until 04/17/2002, being performed six grazings along the time, three in each paddock. The occupation time in each paddock was of one day. The minor resting period was of 33 and the greater of 45 days. In the winter period it was sown, in the space between lines, 110 kg/ha of black oat (Avena strigosa). Seven grazings were performed in this period between 06/12 and 10/14/2002, being three at a paddock and four in another. The occupation time in each paddock was of one day. The minor resting period was of 29 and the greater of 51 days. In both experimentations it was used animals of Holstein breed. The experimental design utilized was randomized blocks in the summer as much as the winter period. The treatments were the grazings performed during the time, and replications the paddocks. The data had been submitted to the analysis of regression with aid of statistical package SAS (1997). Preceding the entrance of the animals in the pasture, samplings of the same one for determination of the dry matter (DM) availability and of the botanical and framework composition were carried through. In the utilization of the pasture for the animals, samples of grazing simulation were collected for posterior analysis of crude protein (CP), fiber in neutral detergent (FND) and dry matter in vitro digestibility (DMIVD). In the summer period the average availability of pasture was of 8257 kg/ha of DM, where the participation of elephantgrass was of 32.5%. The average content of CP, FND and DMIVD of the pasture was of 11.52, 64.15 and 56.67%, respectively. The stocking rate was 2161 kg of live weight/ha. In the winter period the average availability of the pasture was of 3278 kg/ha of DM. The average content of CP, FND and DMIVD of the pasture was of 15.6, 58.6 and 63.92%, respectively. The stocking rate was 1024 kg of live weight/ha